Predicting the potential of wearable technology. - Binkley, P.F (IEEE Engineering in medicine and biology magazine)
The following topics are dealt with: the next era of examination and management of the patient with cardiovascular disease; the importance of technology in rehabilitation; wearable technology applications in Parkinson's disease; wearable sensor technology for functional assessment after stroke.